Triclosan phytoremediation by Glycine max and the rhizobacterium Ochrobactrum sp. MC35 under controlled hydroponic conditions - Sipahutar, Merry Krisdawati; Xuan, Nguyen Thi Kim; Duc, Ha Danh (Universitas Gadjah Mada, 2026)
Triclosan, a common antimicrobial compound, persists in wastewater and sludge because conventional treatment systems do not completely remove it, leading to ecological and health risks. This study investigates the mechanisms of triclosan phytoremediation by Glycine max and its rhizobacterium Ochrobactrum sp. MC35 under controlled hydroponic conditions. A laboratory hydroponic experiment was conducted in which soybean seedlings were exposed to 50–200 µg L–1 TCS, with and without bacterial inoculation. TCS concentrations and metabolites were quantified using LC–MS/MS, while enzymatic activities, including peroxidase, glutathione-S-transferase, laccase and esterase, were measured spectrophotometrically. Degradation kinetics were evaluated using first-order models, and principal component analysis (PCA) was applied to assess correlations among the variables. The combined plant–microbe system achieved 85.4 ± 3.2% triclosan removal within 10 days, nearly twice that of plant-only treatments. Chemical analysis confirmed transient formation of methylated and hydroxylated intermediates, followed by complete degradation through sequential demethylation, hydroxylation and oxidative cleavage pathways. Kinetic modeling exhibited first-order behavior (R2 > 0.96) with an apparent rate constant of 0.312 d–1 in the inoculated system, indicating enhanced microbial degradation. Enzymatic assays showed significant increases in peroxidase, glutathione-S-transferase, laccase and esterase activities, supporting cooperative detoxification between plant and microbe. PCA indicated a close association between enzymatic activity and degradation efficiency, suggesting coordinated rhizospheric interactions. Overall, Glycine max not only absorbed triclosan, but also enhanced its microbial breakdown, likely through exudate-mediated enzyme induction. The findings provide mechanistic insight into bioaugmented phytoremediation and highlight its potential as a sustainable, nature-based strategy for removing persistent antimicrobial pollutants from aquatic environments.